PETRÓLEO Y LITERATURA. UNA MIRADA HISTÓRICA A LA NOVELA VENEZOLANA: (1908-1945) (De la Crítica, 2023)
The present work presents a journey from the theoretical approach of the historiographical vision but with particular attention to what has been contributed from the literary field to the understanding of the oil phenomenon in Venezuela; especially during the 20th century. For this, representative samples are studied both from the literary essay and from the most illustrious novelistic creations that fictionally address the subject. This as a sign that literature always reflects the most decanted thought of the anxieties and interpretations that a people have of their reality.